2014
DOI: 10.1097/aln.0000000000000235
|View full text |Cite
|
Sign up to set email alerts
|

Heat-shock Response Increases Lung Injury Caused by Pseudomonas aeruginosa via an Interleukin-10-dependent Mechanism in Mice

Abstract: Background The heat shock response (HSR) protects from insults, such as ischemia-reperfusion injury, by inhibiting signaling pathways activated by sterile inflammation. However, the mechanisms by which the HSR activation would modulate lung damage and host response to a bacterial lung infection remain unknown. Methods HSR was activated with whole body hyperthermia or by intraperitoneal geldanamycin in mice that had their lungs instilled with Pseudomonas (P.) aeruginosa 24 h later (at least six mice per exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 52 publications
0
11
0
Order By: Relevance
“…The mouse pneumonia model was performed as we previously described [ 56 ]. Mice were instilled with P .…”
Section: Methodsmentioning
confidence: 99%
“…The mouse pneumonia model was performed as we previously described [ 56 ]. Mice were instilled with P .…”
Section: Methodsmentioning
confidence: 99%
“…These results are in line with the findings of Matthay et al, who in 1989 observed that leukotriene B4 instillation in human volunteer lungs resulted in the recruitment of non-damaging neutrophils ( 49 ). Furthermore, Carles et al reported worsened lung injury from pseudomonal pneumonia when sterile inflammation was dampened through the induction of a heat-shock response ( 50 ). These reports are consistent with our findings that inflammation generated by lung IR can augment the host defensive response against bacterial infection.…”
Section: Discussionmentioning
confidence: 99%
“…However, effects of IL-10 on the immune response are highly dependent of the timing and in healthy volunteers challenged with endotoxin, IL-10 displays antiinflammatory properties when it is administered early, but proinflammatory effects when it is injected late (29)(30)(31). Recently, Carles et al (32) demonstrated that heat shock proteins increase the lung injury associated with posttraumatic pneumonia via an IL-10-dependent mechanism. These results are in line with ours because we found an association between high levels of IL-10 after hemorrhage and an overwhelming inflammatory lung response during subsequent pneumonia.…”
Section: Discussionmentioning
confidence: 97%